IMPLEMENTASI METODE WAFᾹ’ PADA PEMBELAJARAN AL-QURAN - Hikmatu Ruwaida (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
Wafa method was born in order to develop Qur’an education system more comprehensively and to make students feel in love with the Qur’an. The context of its instruction aims to make students feel close to Qur’an. This research aims to know about: 1) How is the lesson plan of wafa method on the Qur’an learning? 2) how is the process of wafa method on Qur’an learning? 3) how is the effect of wafa method on the Qur’an recitation and writing skill of students on Integrated Islamic Elementary School of Nurul Fkri Banjarmasin and Integrated Islamic Elementary School of Robbani Banjarbaru, South Borneo. This research is qualitative research by using multicase studies design. The method of data collecting is the interview, participant-observation, and documentation. Techniques of data analysis including single data analysis and cross-data analysis are data reduction, data serving and conclusion. The validity of data is done by observation, triangulation method, peer assessment, discussion, transferability, dependability, and confirmation. The results of this research are : 1) Wafa method that uses in two schools based on four reasons, they are the complexity of instructional goal, effectivity, efficiency and the appropriateness of method with the instructional context and students characteristics; 2) the implementation of Wafa method by using TANDUR concept in two schools is using varying instructional strategy and class management. So, the learning process of the Qur’an was not boring; 3) the effect of this method makes the students be easy to know the alphabet, terms, and spelling of the Qur’an, where is in its practice, it has been customized with the Indonesian grammar that has been mastered by the students. The recitation of Qur’an for all students is good, but there are still some difficulties like reciting the word of gunnah, stressing of some alphabet and jahr sukun alphabet, reciting the similar alphabet of the place of articulation and madd. The ability to write hijaiyah single alphabet and sentence already well within the scope of correct writing, but not to the rules of khat naskhi. Keyword: Wafa Method, Al-Qur’an Learning